Pengaruh Pertumbuhan Penjualan, Intensitas Modal dan Kepemilikan Manajerial Terhadap Penghindaran Pajak - Sasmita, Astuti Indah; Ferdiansyah, Ferdiansyah (-, 2026)
This study aims to determine the effect of Sales Growth, Capital Intensity and Managerial Ownership on Tax Avoidance. The population of this study is consumer non-cyclical companies listed on the Indonesia Stock Exchange in 2019-2023. The number of samples obtained using the purposive sampling technique is 14 companies with observations for 5 years, the number of observations is 70 company data. The research method used is a quantitative method using secondary data, this type of research is associative. While the data analysis technique is panel data regression with the eviews 12 program. The results of this study indicate that simultaneously sales growth, capital intensity and managerial ownership have a simultaneous effect on tax avoidance. While partially sales growth has a negative effect on tax avoidance, capital intensity has a positive effect on tax avoidance, while managerial ownership has no effect on tax avoidance